Distribution of group B Streptococcus isolated from humans in Southeast Asia: a systematic review and meta-analysis - Muthanna, AbdulRahman; Sulaiman, Nurshahira; Dzaraly, Nurul Diana; Al-Obaidi, Mazen M Jamil; Amin-Nordin, Syafinaz; Azmai, Mohammad Noor Amal; Mohd Desa, Mohd Nasir (Wolters Kluwer Medknow Publications, 2025)
Objective: To assess the burden of Group B Streptococcus (GBS) and analyze the distribution of serotypes in relation to their source. The review highlights data gaps in transmission dynamics and regional food consumption practices, which are essential for designing effective public health strategies and advancing vaccine development. Methods: Searches were conducted in Web of Science, MEDLINE, Science Direct, PubMed, and Scopus databases to find studies related to GBS during 1990-2025. Eligible studies were those that described prevalence, serotype distribution or sequence type (ST) of GBS in Southeast Asian countries. Random-effects meta-analysis was used to pool data. Results: A total of 26 studies met the inclusion criteria from eight countries. The pooled estimate of maternal GBS colonization was 15.1%, with serotypes III, V, II, VI, and I a accounting for the majority of cases (91.24%) in the Southeast Asia studies. Data on ST was limited; however, ST1 was found to be predominant in Malaysia and Thailand, while ST283 was notably linked to the consumption of raw fish. Conclusions: The pooled estimate of the maternal colonization with GBS was 15.1% which is equivalent to many other primary and review reports worldwide. Distribution of serotype and ST is needed to be studied in Southeast Asian countries to devise effective preventive measures. These findings underscore the importance of surveillance and tailored prevention strategies to combat GBS infections in Southeast Asia.